1995
DOI: 10.1172/jci118350
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle membrane lipid composition is related to adiposity and insulin action.

Abstract: The cellular basis of insulin resistance is still unknown, however, relationships have been demonstrated between insulin action in muscle and the fatty acid profile of the major membrane structural lipid (phospholipid). The present study aimed to further investigate the hypothesis that insulin action and adiposity are associated with changes in the structural lipid composition of the cell. In 52 adult male Pima Indians, insulin action (euglycemic clamp), percentage body fat (pFAT; underwater weighing), and mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
206
5
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(236 citation statements)
references
References 43 publications
24
206
5
1
Order By: Relevance
“…Although the controversy in earlier data concerning marine fatty acids and glucose metabolism (Salomaa et al, 1990;Feskens et al, 1991Feskens et al, , 1995Borkman et al, 1993;Adler et al, 1994;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Baur et al, 1998;Gustafsson et al, 1998;Bjerregaard et al, 2000;Ekblond et al, 2000;Mori et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004;Thorsdottir et al, 2004) may be partly explained by different doses and durations of supplementation in intervention studies, and by different background diets between the study populations, inclusion of subjects with different PPARG Pro12Ala genotypes could also influence the outcome of the study. That PPARG genotype may affect the associations of dietary fat composition with insulin concentrations (Luan et al, 2001) and serum triacylglycerol response to fish oil supplementation (Lindi et al, 2003) was suggested previously.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the controversy in earlier data concerning marine fatty acids and glucose metabolism (Salomaa et al, 1990;Feskens et al, 1991Feskens et al, , 1995Borkman et al, 1993;Adler et al, 1994;Vessby et al, 1994aVessby et al, , b, 2001Pan et al, 1995;Marshall et al, 1997;Baur et al, 1998;Gustafsson et al, 1998;Bjerregaard et al, 2000;Ekblond et al, 2000;Mori et al, 2000;Hu et al, 2001;Salmeró n et al, 2001;Dewailly et al, 2001a, b;van Dam et al, 2002;Wang et al, 2003;Harding et al, 2004;Thorsdottir et al, 2004) may be partly explained by different doses and durations of supplementation in intervention studies, and by different background diets between the study populations, inclusion of subjects with different PPARG Pro12Ala genotypes could also influence the outcome of the study. That PPARG genotype may affect the associations of dietary fat composition with insulin concentrations (Luan et al, 2001) and serum triacylglycerol response to fish oil supplementation (Lindi et al, 2003) was suggested previously.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been observed that Pima Indians, who are at high risk for TIID, have a lower muscle phospholipid DHA level compared to a Caucasian population (Borkman et al, 1993;Pan et al, 1995). This observation has urged the speculations that genetically determined differences in elongation and desaturation of fatty acids or their incorporation into membranes might contribute to the difference (Pan et al, 1995). Our findings point to a higher conversion rate of ALNA to EPA in female Ala-allele carriers compared to Pro homozygotes, which could be compatible with such a genetic hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations